Karakteristik Jamur Kontaminan Pascapanen pada Beberapa Jenis Umbi – umbian - Rahmiati Rahmiati; Toberni S Situmorang; Helen Anjelina Simanjuntak; Dini Pratiwi; Indah Sari (Herbal Medicine Journal, 2026)
The quality of tuber crops frequently deteriorates as a result of post-harvest fungal contamination. Fungal contamination of potatoes, sweet potatoes, and taro tubers during post-harvest handling and storage can significantly reduce their economic value and pose potential health risks through the production of mycotoxins. This study aimed to evaluate the post-harvest shelf life of potato, sweet potato, and taro tubers and to identify the fungal species contaminating these commodities. A qualitative descriptive approach was employed using the scratch plate isolation method. Fungal contaminants were characterized based on macroscopic colony morphology and microscopic features. The research procedures included sample preparation, assessment of physical quality changes during storage, fungal isolation, and identification. The results demonstrated that taro tubers maintained the highest physical quality after 14 days of storage, whereas potato tubers exhibited the most pronounced physical deterioration and the highest incidence of fungal contamination. A total of eight fungal isolates with distinct macroscopic and microscopic characteristics were obtained, designated as T1SP1, T1SP2, U1SP1, U1SP2, T2SP1, T2SP2, T3SP1, and T3SP2. These isolates were identified as belonging to the genera Aspergillus, Trichoderma, Colletotrichum, and Curvularia.